Notes on the genus Gypsophila (Caryophyllaceae) in Turkey, with a description of G. guvengorkii sp. nov. - Armağan, Meti̇n; Özgökçe, Fevzi̇; Çeli̇k, Ali̇ (Phytotaxa, 2017)
Gypsophila guvengorkii (Caryophyllaceae) is described as a new species from Karabük province, Turkey. Morphology, distribution in Turkey, notes on ecology, and the conservation status are provided, as well as a comparison with the similar species G. brachypetala, G. briquetiana, and G. davisii. Additionally, an emended description of G. brachypetala is given. G. patrinii is excluded from the Flora of Turkey since the specimens collected from Doğubayazıt, which were previously identified as G. patrinii, actually refer to G. transcaucasica, which represents a new record for Turkey.